THE IMPROVING OF HIGHER-ORDER THINKING SKILLS AS INFORMATION FILTER FOR ALPHA GENERATION - Putri, Weni Tria Anugrah; Umah, Restu Yulia Hidayatul (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2020)
This paper's aim is to describe the strategy to improve the ability to think at a higher level for children currently in primary education. Children currently in primary education are children who are in the Alpha generation. This generation is certainly different from previous generations, especially in access to information. Even children holding a device in daily life is not a strange sight. This fact needs to be examined more about the balance in the speed of obtaining information and managing it. The more accessible access to information is, the expectation is children have a good filter for news or information that is classified as reasonable and vice versa, namely information that is classified as not making sense. The ability to filter this information is not easily obtained by every child. In other words, children need a stimulus to be able to think at a high level. The goal is that when children can think at a high level, then that ability is used as a weapon to gain the ability to filter information. In this paper, the focus of discussion is a strategy that should be taught by adults around the children to be able to be wiser in managing information. This research applies a qualitative approach with a literature study. The finding is the ability for the children to think at a higher level can improve with learning through contextual problems. This contextual problem is obtained from daily activities carried out by children